Human T-cell lymphotropic virus type II in Guaraní Indians, Southern Brazil Vírus linfotrópico de células T-humanas do tipo II em Índios Guaraní, Sul do Brasil - Marcio Menna-Barreto; Ana Ligia Bender; Sandro L. Bonatto; Loreta B. Freitas; Francisco M. Salzano; Luiza T. Tsuneto; Maria Luiza Petzl-Erler (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2005)
Human T-cell lymphotropic virus type II (HTLV-II) is found in many New World Indian groups on the American continent. In Brazil, HTLV-II has been found among urban residents and Indians in the Amazon region, in the North. Guaraní Indians in the South of Brazil were studied for HTLV-I/II infection. Among 52 individuals, three (5.76%) showed positive anti-HTLV-II antibodies (enzyme-linked immunosorbent assay and Western blot). This preliminary report is the first seroepidemiological study showing HTLV-II infection among Indians in the South of Brazil. O vírus linfotrópico de células T-humanas do tipo II (HTLV-II) é identificado em muitos grupos de ameríndios. No Brasil, tem sido encontrado em indivíduos da população urbana, bem como em índios oriundos da região Amazônica. Os Índios Guaraní, do Sul do país, foram investigados para infecção por HTLV-I/II. Três indivíduos, oriundos de uma amostra de 52 índios, demonstraram sororeatividade para HTLV-II (ensaio imunoenzimático e Western blot). Este estudo preliminar foi o primeiro a identificar a presença de infecção por HTLV-II em ameríndios do Sul do Brasil.